A Philosophical collision: media ethics meets neuroscience - Muncy, Rhema M., author; Plaisance, Patrick, advisor; Christen, Cindy, committee member; Troup, Lucy, committee member (Colorado State University. Libraries, 2012)
Paving new theoretical pathways often comes at the crossroads of different perspectives uniting to consider questions. Neuroethics is one such lens at the forefront of current media ethics research. This thesis seeks to build theoretical bridges between neuroscience and media ethics, an integration of diverse methodologies to assist in maturation of the field. Neurobiological tools and theories have flanked sociological considerations for several decades, and research in journalistic academia has also begun to integrate these ideas. Decision making from the inside-out is examined through Cognitive Affective Units, Identity Theory, the role of emotions in reasoning and Schema Theory. A sample study design is suggested utilizing Rest's Defining Issues Test developed for fMRI. Other areas suggested for exploration include pedagogy, free will, autonomy and moral development processes.
Keywords: defining issues test; schema theory; neuroethics; fMRI